2015
DOI: 10.1186/s12990-015-0058-6
|View full text |Cite
|
Sign up to set email alerts
|

Alleviating Neuropathic Pain Mechanical Allodynia by Increasing Cdh1 in the Anterior Cingulate Cortex

Abstract: BackgroundPlastic changes in the anterior cingulate cortex (ACC) are critical in the pathogenesis of pain hypersensitivity caused by injury to peripheral nerves. Cdh1, a co-activator subunit of anaphase-promoting complex/cyclosome (APC/C) regulates synaptic differentiation and transmission. Based on this, we hypothesised that the APC/C–Cdh1 played an important role in long-term plastic changes induced by neuropathic pain in ACC.ResultsWe employed spared nerve injury (SNI) model in rat and found Cdh1 protein le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
0
10
1
Order By: Relevance
“…Mutations in this gene are correlated with gastric, breast, colorectal, thyroid and ovarian cancer (OMIM ID: 192090). In addition, studies have shown that CDH1 was expressed highly in the mammalian neurons, and it has the function of regulating synaptic differentiation and transmission [ 39 , 40 ]. CDH1 plays an important role in the development of central nervous system disease [ 40 , 41 ], we deduce the gene CDH1 is correlated with AD.…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in this gene are correlated with gastric, breast, colorectal, thyroid and ovarian cancer (OMIM ID: 192090). In addition, studies have shown that CDH1 was expressed highly in the mammalian neurons, and it has the function of regulating synaptic differentiation and transmission [ 39 , 40 ]. CDH1 plays an important role in the development of central nervous system disease [ 40 , 41 ], we deduce the gene CDH1 is correlated with AD.…”
Section: Resultsmentioning
confidence: 99%
“…The pathology of NeP in patients with low back pain has been attributed to nerve tissue damage generated by mechanical compression or inflammation of the nerve root due to degenerative disc disease [11]. Results from studies in animal models have also suggested that factors such as notch signaling activation [26], transient receptor potential ankyrin 1 (TRPA1) [27], and Cdh1 [28] are involved in the pathogenesis of NeP.…”
Section: Discussionmentioning
confidence: 99%
“…; Tan et al . ). On the basis of ensuring the validity of experimental results, all efforts were made to reduce the number of animals used in our experiments and to minimize any possible suffering by the animals.…”
Section: Methodsmentioning
confidence: 97%